Comparison of retrograde intrarenal surgery and mini-percutaneous nephrolithotomy for lower calyx renal stones - Galeti, Ershad Hussain; Shahab, Saqib; Bharali, Mriganka Deuri; Yakaiah, Rajaboina (Asian Journal of Medical Sciences, 2021)
Background: Due to the anatomic characteristics of the lower calyx, lower polar stones are difficult to be removed through the ureter, retrograde intrarenal surgery (RIRS) can be used to deal with lower polar stones, while mini-percutaneous nephrolithotomy(mini-PCNL) is mainly used to deal RIRS failed to eliminate the stone. Aims and Objectives: Prospective comparison of mini-PCNL and retrograde intrarenal surgery outcomes in lower calyx management with respect to surgery duration, pain score (visual analog score), analgesic requirement, hemoglobin drop, and hospital stay. Materials and Methods: This is a prospective study in 50 patients (25 cases of RIRS and 25 cases of MINIPERC) over 2 years who came to the urology departme with lower calyx stone of size up to 20mm. The selection of the management methods was primarily based on the patient’s preferences. Preoperatively, all patients underwent routine workup and CT KUB plain. The primary and secondary objective was stone clearance rates, retreatment rate, complications, surgical duration, pain score (visual analog score [VAS]), analgesic requirement, hemoglobin drop, and hospital stay. Results: Miniperc and RIRS had stone clearance rates of 100% and 96%, respectively. In the RIRS group, one patient required retreatment for 1month. Hospital stay, intraoperative and post-operative complications were non-significant between both groups. Operative duration (P=0.003) was lower in the Miniperc group. Hemoglobin drop (P<0.0013), patient pain, and visual analog scale score at 6, 24, and 48 h, as well as an analgesic requirement (P<0.020), were all lower in the RIRS group. Conclusion: The stone clearance rates in both modalities are high, and complications are low. RIRS requires a longer operative duration, and it is associated with favorable pain scores and a lower hemoglobin drop.